Religious freedom, religious discrimination and the workplace - Vickers, Lucy (Oxford Portland, Oregon Hart Publishing, 2016)
Religious discrimination and religious freedom at work -- Seeking a definition of religion and belief -- Protecting religion at work -- Freedom of religion at work : the European dimension -- Protection against religion and belief discrimination in the UK -- Accommodating religion and belief in the workplace: North American perspectives -- Conclusion : religious freedom at work
B
Keywords: Great Britain; Freedom Of Religion; Religion in the workplace -- Law and legislation -- Great Britain; Freedom Of Religion -- Great Britain; Religion in the workplace -- Law and legislation; Religion in the workplace -- Law and legislation; Religion in the workplace -- Law and legislation -- Great Britain; Discrimination -- Religious aspects; Discrimination in employment -- Law and legislation -- Great Britain